Searching for PeV neutrinos from photomeson interactions in magnetars. (4th November 2016) - Dey, Rajat K.; Ray, Sabyasachi; Dam, Sandip
Abstract: In this paper we estimate the flux of PeV neutrinos and gamma-rays from magnetar polar caps, assuming that ions/protons are injected, and accelerated in these regions and interact with the radiative background. The present study takes into account the effect of the photon splitting mechanisms that should modify the radiative background, and enhance the neutrino and gamma-ray fluxes at PeV energies, with a view to explain the PeV neutrino events detected in IceCube. The results indicate that in the near future, the possibility of any significant excess of neutrino events from a magnetar in the Milky Way is extremely low. Further, we suggest that the simultaneous observation of neutrinos and gamma-rays at Earth from expanded "Gen2" IceCube detector and/or High Altitude Water Cherenkov Observatory would provide opportunities to explore the possible origin of very high-energy neutrinos and gamma-rays.